2001
DOI: 10.1046/j.1469-0705.2001.abs25-5.x
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in estimating fetal urinary bladder volume using a modified ultrasound technique

Abstract: Objective: To evaluate the accuracy and assess the indications of fetal echocardiography to diagnose structural heart disease in our high risk population, by an obstetric team. Methodology: Over a 4-year period, a transabdominal echocardiography was performed in 912 high risk pregnancies for congenital heart disease at 18-38 weeks of gestation. In the last 140 cases, an early examination combining either the transvaginal or the transabdominal route at 13-16 weeks was also carried out. Follow up was obtained fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 0 publications
2
10
1
Order By: Relevance
“…They calculated bladder volume by rotating the longitudinal fetal bladder shape around its long axis. Using this method they reported that the standard deviation was reduced to 3.5–8.8%, compared with 5.5–12.5% using the ellipsoid formula16. Although this method provided a more accurate estimation than the ellipsoid formula, as it is independent of longitudinal bladder shape, it is nevertheless based on the assumption that the bladder is a rotational body around its long axis.…”
Section: Discussionmentioning
confidence: 99%
“…They calculated bladder volume by rotating the longitudinal fetal bladder shape around its long axis. Using this method they reported that the standard deviation was reduced to 3.5–8.8%, compared with 5.5–12.5% using the ellipsoid formula16. Although this method provided a more accurate estimation than the ellipsoid formula, as it is independent of longitudinal bladder shape, it is nevertheless based on the assumption that the bladder is a rotational body around its long axis.…”
Section: Discussionmentioning
confidence: 99%
“…The study material comprised longitudinal fetal bladder images, which were used in a previous 2D ultrasound study7 in 1998–1999 conducted at the Department of Obstetrics and Gynaecology, North Elfsborg County Hospital, Trollhättan, Sweden. The gestational ages were between 24 and 40 weeks and 34 fetuses (all singletons) were included.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, the identical images from the aforementioned7 study were re‐evaluated at the same institution in 2000–2001. Using identical bladder images, SD ‘total error straight sequence ’ and SD ‘frozen error one image ’ were estimated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…AF volume is determined by several factors4, and any disturbance in the regulatory mechanism can induce polyhydramnios. Fetal urine production can be measured by serial assessment of bladder volume with two‐dimensional5–18 and, as described more recently, three‐dimensional19–22 ultrasound. We undertook this study to evaluate whether measurement of the urine production rate (UPR) in fetuses with increased AF volume can be used to differentiate the causes of polyhydramnios.…”
Section: Introductionmentioning
confidence: 99%